A Fault Detection Method and a Tolerance Control in a Single-Phase Cascaded H-bridge Multilevel Inverter. Issue 1 (July 2017) - Lee, June-Hee; Lee, Kyo-Beum
Abstract: This paper proposes a fault detection method and a tolerance control in a single-phase cascaded H-bridge multilevel inverter (CHBMI). In case of open-fault, the body diode of the fault switch provides a freewheeling current path. However, in case of short-fault, the freewheeling current path cannot be described by disconnecting of fuse and the distortion of output current is different from that of open-fault. Therefore, it is possible to separately detect the type of fault. When the open-fault or short-fault occurs, the output phase voltage has to limit because the single-phase CHBMI unable to compensate from another phase voltage like three-phase systems. Therefore, the reference voltage has to reconfigure, and the tolerance control is operated depending on the different fault types. In the proposed detection method, it is possible to detect not only the fault cell number but the fault location of switch accurately, and the quality of output current can improve through the proposed tolerance control when both open-fault and short-fault occur. The effectiveness and performance of proposed fault detection and tolerance control method are verified by simulation results.